Basal Cisternostomy for Severe TBI: Surgical Technique and Cadaveric Dissection - Giammattei, L.; Starnoni, D.; Messerer, M.; Daniel, R. T. (Frontiers in Surgery, 2022)
Introduction Cisternostomy is emerging as a novel surgical technique in the setting of severe brain trauma. Different surgical techniques have been proposed with a variable degree of epidural bone work. We present here the surgical technique as it is currently performed in our Institution. Methods Anatomical dissection of one adult cadaveric head, injected and non-formalin fixed was perfomed. A large right fronto-temporo-parietal craniotomy was accomplished. Extradural sphenoidal drilling till opening of the superior orbital fissure was performed. The microsurgical anatomy of basal cisternostomy was then explored. Results A step by step description of the surgical technique, enriched with cadaveric and intraoperative images, was made. Conclusion Basal cisternostomy is a promising surgical technique that does not necessarily include complex surgical maneuvers. Trained neurosurgeon can safely implement it in their clinical practice.